Satiriska feministiska serier: Nina Hemmingsson och Liv Strömquist - Lindberg, Ylva (Tidskrift för litteraturvetenskap, 2014)
Satiric Feminist Comic Art. Nina Hemmingsson and Liv Strömquist This article focuses on the satiric works of the contemporary Swedish female cartoonists Nina Hemmingsson and Liv Strömquist, particularly on their potential to be read and interpreted on a literary level. The development of comic arts in Sweden during the last decade indicates in fact that comics are not only a product of ephemeral entertainment or a subculture for some happy few. Literary analysis presuppose a complex piece of work, which invites the reader to different interpretations. Some of these levels of sense making are revealed in this study on how Hemmingsson and Strömquist transmit feminist messages through text and image. In the first case, the theoretical frame used in the analysis is based on Bakhtin’s aesthetics of the grotesque. In the second case, post-colonial theories represented by Fanon, reveal how Strömquist criticize heteronormativity and power positions in society.